2003
DOI: 10.1161/01.str.0000085087.41330.ff
|View full text |Cite|
|
Sign up to set email alerts
|

Persistent Poststroke Hyperglycemia Is Independently Associated With Infarct Expansion and Worse Clinical Outcome

Abstract: Background and Purpose-Hyperglycemia at the time of ischemic stroke is associated with increased mortality and morbidity. Animal studies suggest that infarct expansion may be responsible. The influence of persisting hyperglycemia after stroke has not previously been examined. We measured the blood glucose profile after acute ischemic stroke and correlated it with infarct volume changes using T2-and diffusion-weighted MRI. Methods-We recruited 25 subjects within 24 hours of ischemic stroke symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
364
2
19

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 555 publications
(403 citation statements)
references
References 59 publications
(47 reference statements)
18
364
2
19
Order By: Relevance
“…The CGM device has recently been used to examine the detailed dynamic state in diabetic patients with simple and safe installation. Baird et al1 examined blood glucose levels using the CGM in 25 patients with anterior circulation stroke syndrome; only mean blood glucose level was measured as a glucose parameter to examine its relationship to poor outcomes. Ribo et al22 showed that the longer duration of blood glucose ≥140 mg/dL on the CGM and the longer time to middle cerebral artery recanalization after intravenous thrombolysis were related to unfavorable outcomes at 3 months in 47 ischemic stroke patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CGM device has recently been used to examine the detailed dynamic state in diabetic patients with simple and safe installation. Baird et al1 examined blood glucose levels using the CGM in 25 patients with anterior circulation stroke syndrome; only mean blood glucose level was measured as a glucose parameter to examine its relationship to poor outcomes. Ribo et al22 showed that the longer duration of blood glucose ≥140 mg/dL on the CGM and the longer time to middle cerebral artery recanalization after intravenous thrombolysis were related to unfavorable outcomes at 3 months in 47 ischemic stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…Elevation of blood glucose levels caused activation of the coagulant system, suppression of the fibrinolytic system, and production of free radicals 26, 28, 29, 30, 31. This elevation may also lead to acidosis, excitatory amino acids, and injury to the blood–brain barrier, which cause ischemic brain damage in animal models and expand ischemic lesions volumetrically 1, 23, 25, 32. Expanding lesions may lead to production of cortisol and norepinephrine, which worsen hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Using this technology, Baird et al performed a pilot study in which they aimed to directly address the relationship between stroke outcome and contemporaneous glycaemia [37]. This trial enrolled 25 subjects within 24 hours of ischaemic stroke symptoms.…”
Section: Lessons From Continuous Glucose Monitoringmentioning
confidence: 99%
“…This relation is now known to be independent of other predictors of poor clinical outcome, such as stroke severity score, infarct size, age, or having diabetes [36]. In the Glycemia in Acute Stroke (GLIAS) trial [37], it was found that an elevated glucose of more than 155 mg/dL in the first 48 hours after an acute ischemic stroke was associated with a 2.7-fold increase in poor functional outcome, and there was a 3-fold increase in the risk of death at 3 months [37].…”
Section: Hyperglycemia In the Stroke Patientmentioning
confidence: 98%